(untitled) (DAPesquisa, 2025)
This article presents the Conceptual Adherence Matrix (CAM) as a tool to support the process of authorial fashion design, understood as a creative expressive practice closely related to the artistic field. The methodology combines theoretical review and experiential reporting, illustrated by a student’s practical application. The theoretical foundation draws on studies of visual expressiveness (Perassi, Dondis, Gomes) and specific clothing attributes (Jones, Campos, Sanches), articulating references from both visual arts and fashion design. CAM enhanced the conceptual structuring of collections and the reinforcement of students’ critical autonomy by providing evaluation parameters aligned to the collection’s concept. Its adaptable structure allows it to be applied to different contexts and to be combined with other design tools, such as the Expressive Categories Map (Sanches, 2017).